Global assessment of shark strandings. Issue 4 (17th February 2022) - Wosnick, Natascha; Leite, Renata D.; Giareta, Eloísa P.; Morick, Danny; Musyl, Michael
Abstract: Marine wildlife stranding is a global phenomenon, and for some taxonomic groups, these events are well monitored and documented. Although sharks are among the most threatened vertebrates, strandings have historically been neglected, with little information on this topic currently available. To address this knowledge gap, a systematic review on scientific publications from indexed databases, multimedia material and citizen science databases was performed. A total of 3150 reports were recovered, with strandings dating back to 1880 including 89 species of sharks from 22 families. Both single/small‐scale and mass stranding events were observed. Species ranged from coastal to oceanic, with reports for small‐, medium‐ and large‐sized sharks. Leopard ( Triakis semifasciata, Triakidae), brown smooth‐hound ( Mustelus henlei, Triakidae) and salmon sharks ( Lamna ditropis, Laminidae) were the species with most records. Females stranded significantly more than males, but juveniles and adults were affected in the same proportion. Shark strandings were reported for 47 countries, and the United States was the most representative location, highlighting the states of California and Oregon. Survival rates were extremely low, indicating that stranded sharks are more vulnerable that other taxonomic groups. Potential and putative causes were identified, being similar to those suggested for marine mammal strandings. Our results indicate that although they occur to a lesser extent when compared to mammals, shark strandings are neglected, and urgent measurements are necessary to better understand, document and to properly respond to these events.